Fermentasi Rasio C/N pada Limbah Cair Tempe Menggunakan Bakteri Pseudomonas sp terhadap Parameter pH, Kadar Nitrogen, dan Total Bakteri - Indah Lusitasari (FT-USNI, 2019)
Tempe industry is one type of industry that produces liquid waste which can cause pollution if it is not managed properly because it contains high enough organic compounds, to overcome these problems then the idea arises to utilize tempe liquid waste to become a useful final product by managing it. as organic liquid fertilizer which is useful for fertilizing plants. This study aims to determine the pH, nitrogen and total bacterial content of tempe wastewater fermentation in this study. In this study there were two treatments, namely the processing of tempe liquid waste without bacteria (blank), the processing of liquid tempeh with the addition of the bacterium Pseudomonas sp. Analysis of fertilizer quality parameters such as pH, nitrogen and totalbacteria.